Opening up the family archive - Kirk, Dave; Izadi, Shahram; Sellen, Abigail; Taylor, Stuart; Banks, Richard; Hilliges, Otmar (Proceedings of CSCW 2010, 2010)
The Family Archive device is an interactive multi-touch tabletop technology with integrated capture facility for the archiving of sentimental artefacts and memorabilia. It was developed as a technology probe to help us open up current family archiving practices and to explore family archiving in situ. We detail the deployment and study of three of these devices in family homes and discuss how deploying a new, potentially disruptive, technology can foreground the social relations and organizing systems in domestic life. This in turn facilitates critical reflection on technology design.
Winner Best Paper CSCW